Development of The Morning Pteridophyta Based on The Local Potential of Mangkunagoro I Forest Park for Grade X Students - Yessy Ratna Siwie; Nurmiyati Nurmiyati; Alanindra Saputra (Universitas Sebelas Maret, 2020)
The Pteridophyta is one of the topics studied by the tenth graders, which is also included in the National Final Examination for High School. Based on several related studies, student's scores on this material were still low. One effort to overcome this problem is to make innovative learning media. In this study, we explore the development of the Morning (Mobile learning) App about Pteridophyta by utilizing the local potentials and Pteridophyta diversity found in Mangkunagoro I Forest Park. Purpose: This research was aimed to 1) develop the Morning (mobile learning) App about Pteridophyta for the tenth grader based on the local potentials found in Mangkunagoro I Forest Park; 2) determine the feasibility of the morning app as learning media, 3) find out the student's responses toward the app. Methods: This research was research and development. The ADDIE development model was used as the method. It consisted of (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The data were collected by using questionnaires for content (subject matter) experts, media experts, and teachers. Data were analyzed by using descriptive analysis and RASCH analysis for student responses. The population of this study was all tenth graders at Surakarta 7 High School academic year 2019/2020. Samples were taken using the purposive sampling technique. Result: The results showed that 1) Morning app for Pteridophyta has been developed according to ADDIE procedures arranged by incorporating the local potentials and diversity of Pteridophyta found in the Mangkunagoro I Forest Park, 2) Morning app for Pteridophyta was qualified as